POA OPINATA (GRAMINEAE), A NEW SPECIES FROM G. BINAIYA, CERAM, MOLUCCAS, INDONESIA - VELDKAMP J.F. (REINWARDTIA, 2017)
VELDKAMP, J. F. 2017. Poa opinata (Gramineae), a new species from G. Binaiya, Ceram, Moluccas, Indonesia. Reinwardtia 16 (2): 73–75. — Poa species is described from Ceram, Moluccas and compared to Poa languidior from New Guinea.